Implikasi Hukum Bisnis Terhadap Praktik Etika Bisnis Di Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This research aims to analyze the implications of business law on business ethics practices in Indonesia. The research method used is library research, where data is collected from various literature sources that are relevant to the research topic. The research results show that business law has an important role in shaping business ethical practices in Indonesia. Business law regulates the rights and obligations that arise from agreements and engagements in business practices. In addition, factors such as national development developments, business ethics, internal and external factors, and legal awareness influence the implementation of business law in ethical and responsible business practices. Therefore, the solutions and recommendations provided to improve the implementation of business law and ethical business practices in Indonesia include strengthening regulations, effective law enforcement, education and awareness, collaboration between government and the business world, transparency and accountability, and the establishment of a supervisory body. independent. It is hoped that the implementation of this solution can create a business environment that is fair, transparent and has integrity, as well as making a positive contribution to economic development and social welfare in Indonesia.